Estimation of Rooftop Rain Water Harvesting Potential by Water Budgeting Study - Manikandan, M.; Ranghaswami, M. V.; Thiyagarajan, G. (International Journal of Bio-resource and Stress Management, 2023)
In the present era of acute water shortage both in rural areas for agriculture and urban areas for drinking and industrial water needs, rainwater harvesting seems to be feasible solution to provide for considerable storage of water during rains. The water budgeting study was conducted to know the rainwater harvesting potential for office/departments buildings in TNAU campus by considering rainfall as the only source of supply of water. The weekly water demands and water supplies by rain water were worked out. The period of surplus or deficit of water can be found out by comparing the total supply and the total demands for any week. From the water budgeting calculation, the total annual water requirement was found to be 306.15 ha cm and water harvesting potential was calculated as 255.59 ha cm. The potential period for rainwater harvesting was found to exist from 37th to 47th week. Temporary surplus water which can be stored in rainwater harvesting structure during rainy season were estimated as 146.29 ha cm. It was also found that seasonal water demand was more than seasonal rainwater supply in the first and third season whereas in second season the demand was very less compared to rainwater supply in office/departmental areas due to north east monsoon. The annual water demand was more than the annual water supply by rain water. The additional water required to overcome these deficit has to be managed through external water supply and groundwater pumping. The water harvesting potential, which was calculated from water budgeting analysis, can be effectively stored in water harvesting structures and beneficially used for supplemental irrigation, scientific lab purpose, drinking water needs of human beings and animals and other categories of water usage within the campus.